2014
DOI: 10.1088/0957-0233/25/9/095204
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous two-phase flow measurement of spray mixing process by means of high-speed two-color PIV

Abstract: In this article, a novel high-speed two-color PIV optical diagnostic technique has been developed and applied to simultaneously measure the velocity flow-fields of a multi-hole spark-ignition direct injection (SIDI) fuel injector spray and its ambient gas in a high-pressure constant volume chamber. To allow for the phase discrimination between the fuel droplets and ambient gas, a special tracer-filter system was designed. Fluorescent seeding particles with Sauter mean diameter (SMD) of 4.8 µm were used to trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 24 publications
3
41
1
Order By: Relevance
“…There is very limited information in the existing literature on the application of twophase PIV over a range of conditions and fuel types. Some interesting information can be found in [37] where spray-flow interactions were studied with n-pentane and it was observed that there was stronger momentum transfer from the liquid spray to the ambient with increased fuel superheat. The effect was attributed to the expanded spray plumes of the multihole injector that was used and the smaller droplet sizes, which increased the interaction area between the two phases before the spray collapsed, as well as to the undisturbed velocity core around the injector axis area after the spray had collapsed.…”
Section: Flow Field and Tke At Ignition Timing With Fuel Injectionmentioning
confidence: 99%
“…There is very limited information in the existing literature on the application of twophase PIV over a range of conditions and fuel types. Some interesting information can be found in [37] where spray-flow interactions were studied with n-pentane and it was observed that there was stronger momentum transfer from the liquid spray to the ambient with increased fuel superheat. The effect was attributed to the expanded spray plumes of the multihole injector that was used and the smaller droplet sizes, which increased the interaction area between the two phases before the spray collapsed, as well as to the undisturbed velocity core around the injector axis area after the spray had collapsed.…”
Section: Flow Field and Tke At Ignition Timing With Fuel Injectionmentioning
confidence: 99%
“…PIV spray measurements are described in [195,196]. Zhang et al reported high-speed PIV measurements with 6 kHz using pulsed illumination [197]. Time-resolved DGV spray measurements were performed with continuous-wave illumination by Fischer et al [83].…”
Section: Application Examples Challenges and Perspectivesmentioning
confidence: 99%
“…An inherent challenge for simultaneous two-phase velocity measurement in this case is due to significantly large velocity difference between the injected droplets and the entrained air flow (for the spray the velocity is of the order of 100 ms −1 in comparison to the gas velocity which is about 1-10 ms −1 ). Accordingly, the laser separation time for PIV application is smaller than 10 µs for the spray, while that for the gas flow lies in the range from tens of microseconds to hundreds of microseconds [65,66,67,68]. The choice of same separation time for both phases can lead to inaccuracy in velocity measurements for both phases.…”
Section: Dense Spray Measurementsmentioning
confidence: 99%